2016
DOI: 10.1002/alr.21717
|View full text |Cite
|
Sign up to set email alerts
|

Connexin gap junction channels and chronic rhinosinusitis

Abstract: The majority of the connexin family is expressed in normal sinus mucosa. Expression of 3 selected connexins was found elevated in CRS mucosa. Connexin gap junction modulation may offer a novel therapeutic target for CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Gap junctions are also components of the innate immunity defence system by mediating the cell-to-cell spread of pro-inflammatory and pro-apoptotic signals according to the pathogen recognition receptors (PRRs) activated [ 18 , 19 ]. Hence, connexins and Panx1 are deregulated in terms of activity and/or expression in several pathologies, including chronic rhinosinusitis [ 20 ] and cystic fibrosis [ 21 , 22 ].…”
Section: Connexins In Normal and Repairing Airway Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junctions are also components of the innate immunity defence system by mediating the cell-to-cell spread of pro-inflammatory and pro-apoptotic signals according to the pathogen recognition receptors (PRRs) activated [ 18 , 19 ]. Hence, connexins and Panx1 are deregulated in terms of activity and/or expression in several pathologies, including chronic rhinosinusitis [ 20 ] and cystic fibrosis [ 21 , 22 ].…”
Section: Connexins In Normal and Repairing Airway Epitheliummentioning
confidence: 99%
“…Re-establishment of the integrity of the airway epithelium is a prerequisite to restoration of the tissue homeostasis and host-defence mechanisms [ 20 ]. The tracheobronchial airway epithelium is composed of BCs, GCs and CCs.…”
Section: Connexins In Normal and Repairing Airway Epitheliummentioning
confidence: 99%
“…Together, these junction proteins function to limit intercellular passage of fluid and protect the underlying tissue from exposure to noxious and allergenic stimuli (London and Ramanathan, 2017). Epithelial cell communication is mediated via Gap junction channels, which are formed by connexin proteins enabling cell communication (Kim et al, 2016). Expression of connexins have been demonstrated to be increased in CRS compared to controls (Kim et al, 2016).…”
Section: Upper Airway Epithelial Functions During Ar and Crsmentioning
confidence: 99%
“…Epithelial cell communication is mediated via Gap junction channels, which are formed by connexin proteins enabling cell communication (Kim et al, 2016). Expression of connexins have been demonstrated to be increased in CRS compared to controls (Kim et al, 2016). Hence, epithelial barrier dysfunction may contribute to AR and CRS through allowing increased passage of antigens and exposure of underlying tissue to these stimuli (Toppila-Salmi et al, 2015;London and Ramanathan, 2017).…”
Section: Upper Airway Epithelial Functions During Ar and Crsmentioning
confidence: 99%
“…A recent report revealed that 16 connexin genes are expressed in the human sinus mucosa [ 3 ]. One report found that connexin-43 is significantly upregulated in CRS patients compared to healthy controls at both the mRNA and protein levels, whereas other reports searching for a potential cause of dysfunction in the sinonasal epithelium failed to find a significant difference in the expressions of connexin-26, -30, -32, or -43 [ 3 5 ]. Although the relationship between CRS and connexin expression is still controversial, those reports have consistently shown that connexin-43 is expressed in human nasal epithelial cells.…”
mentioning
confidence: 99%